Government Oversight Function in Implementation of Large-Scale Social Limitation of COVID-19 in Indonesia - Kaharuddin Kaharuddin (Administrative Law and Governance Journal, 2020)
Indonesia is one of the country that get the big impact because of COVID-19. This COVID-19 have been declared as pandemic by WHO. Indonesia use the Large-scale Social Limitation as their way to prevent the increase of people get infected because of this pandemic. This study will examine the oversight of implementation of Large-scale Social Limitation in Indonesia from the eyes of government. Also, will examine how the government using their power in the middle of this pandemic. In the end, we will know what really government do and how the oversight running. The result of the study are, first,  The government is the party that has the right to design, create, and implement regulations in people's lives. Government can control the society with the regulations that are made by them. Second, Government has obligations to serve the best service for their people. In general, government services include public services and civil services which are respect to the equality. The Government of Indonesia issued several policies such as Presidential Decree (Keppres) Number 7 of 2020 concerning the Task Force for the Acceleration of Covid-19 Handling (amended through Presidential Decree (Keppres) No. 9 of 2020.), Government Regulations (PP) Number 21 Year 2020 concerning Large-Scale Social Restrictions (PSBB) in the framework of the Acceleration of Covid-19 Handling.